INTEGRASI DATA DENGAN WEB SERVICE PADA APLIKASI INDEKOST ONLINE BERBASIS WEBSITE DAN MOBILE - Ardi Sugiarto; Tony Tony; Bobby Tumbelaka (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
The information system which until now growing rapidly create all the jobs in this life many who have gone aided by information technology. The technology can help more easily, quickly, safely and effectively clear it is helpful to anyone who use it. Including to assist students in finding a boarding house when they study / lectures as well as the owner of the boarding house in home market. The need for a boarding house is important, since the students who did the study for a long time and needed a place to stay in the area. And it makes the issue of how these students can seek the appropriate boarding houses, given some constraints such as do not know the area, or have a friend who can demonstrate appropriate boarding house for students.The management system is a system that embodies or can be a friend to the students who feel confused in finding an appropriate boarding houses as well as assist in marketing the owner of a boarding house online. System focused in finding the appropriate criteria for boarding up with the booking to boarding room can be done with this system. Success in implementing this system is to work well to help the students in the search for the location of the appropriate boarding house. From the search, until the online booking can be done with media E-mail. As well as providing benefits to the owner of the boarding house to be able to market the house fullest.